Synthesis, structures and spectroscopy of three new lanthanide β-diketonate complexes with 4,4′-dimethyl-2,2′-bipyridine. Near-infrared electroluminescence of ytterbium(III) complex in OLED - Santos, Hudson P.; Gomes, Emmanuel S.; dos Santos, Molíria V. [UNESP]; D'Oliveira, Kaíque A.; Cuin, Alexandre; Martins, Jefferson S.; Quirino, Welber G.; Marques, Lippy F. (Elsevier, 2019)
Three new lanthanide(III) β-diketonate complexes [Ln(btfa)3(4,4′-dmbpy)] (Ln = Yb(III), Gd(III) and Nd(III); btfa = anionic 4,4,4-trifluoro-1-phenyl-1,3-butanedione and 4,4′-dmbpy = 4,4′-dimethyl-2,2′-bipyridine) were synthesized and their characterization, including elemental analysis, FTIR spectroscopy and thermal analysis (TG/DTA), is reported. The crystal description based on powder X-ray diffraction reveals that Gd(III) and Yb(III) compounds are isostructural and that lanthanide ion is eight-coordinated by oxygen and nitrogen atoms to give new tris- β-diketonates [Ln(btfa)3(4,4′-dmbpy)]. The cell parameters of Nd(III) complex are close to Gd(III) and Yb(III) ones. Phosphorescence data of Gd(III) complex shows that the triplet states (T1) of the ligands have higher energy than the emitting states of Yb(III) and Nd(III), indicating the possibility of intramolecular energy transfer to these metal ions, which exhibit near-infrared (NIR) emission. We have used the Yb(III) complex as an emitting layer (EML) in a near infrared organic light emitting diode (NIR-OLED) with the structure: CuPc(15 nm)/XD-03(40 nm)/Yb(60 nm)/BCP(15 nm)/Alq3(10 nm)/Al(120 nm). OLEDs exhibit both visible electroluminescence and a NIR electroluminescence at 980 nm from the 2F5/2 → 2F7/2 transition of the Yb(III).
Keywords: Lanthanides; Luminescence; OLED; Photophysical properties